Bioactive terpenoids derived from plant endophytic fungi: An updated review (2011–2020). (May 2022) - Amirzakariya, Bahman Zamani; Shakeri, Abolfazl
Abstract: Plant endophytes have been considered as novel sources of naturally occurring compounds with various biological activities, including cytotoxic, antimicrobial, anti-inflammatory, anticancer, herbicides, antileishmanial and antioxidant. A variety of specialised products, comprising terpenoids, alkaloids, polyketides, phenolic compounds, coumarins, and quinone derivatives have been reported from various strains. An increasing number of products, especially terpenoids, are being isolated from endophytes. Herein, the isolated new terpenoids from plant endophytic fungi, their hosts, as well as biological activities, from January 2011 until the end of 2020 are reviewed. In this period, 516 terpenoids are classified into monoterpenes (5), sesquiterpenes (299), diterpenes (76), sesterterpens (22), meroterpenes (83), triterpenes (29), and other terpenoids (2), were isolated from different plant endophytic fungi species. Graphical abstract: Image 1 Highlights: This review article provides over 500 terpenoids derived from plant endophytes from 2011 to 2020. The diverse structures with various biological activities are summarized. Sesquiterpenoids (59%) were the most abundant terpenoids produced by endophytic fungi. Trichoderma was the principal fungal endophytes as producers of terpenoids.